Grandma's gift - Velasquez, Eric (Walker, 2010)
The author describes Christmas at his grandmother's apartment in Spanish Harlem the year she introduced him to the Metropolitan Museum of Art and Diego Velazquez's portrait of Juan de Pareja, which has had a profound and lasting effect on him.